A study of Salmonella prevalence in pork value chain from pig slaughterhouses to markets in Hung Yen, Vietnam - Yokozawa, T. (Rakuno Gakuen University, 2014)
Salmonella which exists in livestock intestine is one of important hazardous pathogens causing food poisoning, and most salmonellosis cases in humans occur due to consumption of contaminated animal origin foods such as meat and eggs. In Vietnam, pork is the most consumed meat and contamination of pork with Salmonella spp. is serious public health problem. This study aimed to trace the value chain forward from pig slaughterhouses to the markets in order to elucidate the dynamics of Salmonella contamination on pork value chain in Hung Yen, Vietnam. This survey was conducted in February 2014 in two slaughterhouses which were randomly selected from the list of slaughterhouses in Hung Yen province and swab samples were collected from 88 carcasses after split there. Out of them, 21 carcasses were traced to the markets and pork samples were collected. Microbial tests were performed for the presence of Salmonella from carcass samples at slaughterhouses. MPN was determined in addition to the presence of Salmonella for pork in markets. For comparison of two slaughterhouses, there was no significant difference in the prevalence of pig carcass samples between them (22.2% (10/45), and 27.9% (12/43), x2=0.18, df=1, p=0.71). In addition, there was also no significant difference between the prevalence on carcasses and pork (25.0% (22/88), and 28.6% (6/21), x2=0.0034, df=1, p=0.95). There was transition of status of Salmonella contamination on pork but kappa value was 0.53 which means there was substantial agreement between the prevalence in slaughterhouses and in markets. MPN of positive pork samples was in the range of <3.0 to 15 MPN/g. In Hung Yen, Salmonella prevalence on pork was high and it was suggested that the level of hygiene at meat processing was not adequate. The prevalence was kept in the same level at between slaughterhouse and market, and it was found that contamination mainly occurred before the end of slaughtering. In this study, only the slaughterhouses processing pig carcasses on the floor were studied. In considering effective improvement of hygiene, a comparison of microbiological study with the other type of slaughterhouses using hanging style, maybe needed, to examine its efficacy in hygiene, as contamination of pork with Salmonella can easily occur on the floor of slaughterhouses.